Pre‐hospital thrombolysis in ST‐segment elevation myocardial infarction: a regional Australian experience. Issue 3 (1st August 2016) - Khan, Arshad A; Williams, Trent; Savage, Lindsay; Stewart, Paul; Ashraf, Asma; Davies, Allan J; Faddy, Steven; Attia, John; Oldmeadow, Christopher; Bhagwandeen, Rohan; Fletcher, Peter J; Boyle, Andrew J
Abstract: Objective: The system of care in the Hunter New England Local Health District for patients with ST‐segment elevation myocardial infarction (STEMI) foresees pre‐hospital thrombolysis (PHT) administered by paramedics to patients more than 60 minutes from the cardiac catheterisation laboratory (CCL), and primary percutaneous coronary intervention (PCI) at the CCL for others. We assessed the safety and effectiveness of the pre‐hospital diagnosis strategy, which allocates patients to PHT or primary PCI according to travel time to the CCL. Design, setting and participants: Prospective, non‐randomised, consecutive, single‐centre case series of STEMI patients diagnosed on the basis of a pre‐hospital electrocardiogram (ECG), from August 2008 to August 2013. All patients were treated at the tertiary referral hospital (John Hunter Hospital, Newcastle). Main outcome measures: The primary efficacy endpoint was all‐cause mortality at 12 months; the primary safety endpoint was bleeding. Results: STEMI was diagnosed in 484 patients on the basis of pre‐hospital ECG; 150 were administered PHT and 334 underwent primary PCI. The median time from first medical contact (FMC) to PHT was 35 minutes (IQR, 28–43 min) and to balloon inflation 130 minutes (IQR, 100–150 min). In the PHT group, 37 patients (27%) needed rescue PCI (median time, 4 h; IQR, 3–5 h). The 12‐month all‐cause mortality rate was 7.0% (PHT, 6.7%; PCI, 7.2%). The incidence of major bleeding (TIMI criteria) in the PHT group was 1.3%; no patients in the primary PCI group experienced major bleeding. Conclusion: PHT can be delivered safely by paramedical staff in regional and rural Australia with good clinical outcomes.